Ocena częstości występowania bólu kręgosłupa oraz stylu i jakości życia wśród osób z bólem kręgosłupa = Evaluation of the prevalence of back pain as well as the style and the quality of life among people with back pain - Kozłowski, Piotr; Kożuch, Katarzyna; Kozłowska, Magdalena; Ławnicka, Izabela; Kozłowska, Karolina (Journal of Education, Health and Sport, 2016)
Kozłowski Piotr, Kożuch Katarzyna, Kozłowska Magdalena, Ławnicka Izabela, Kozłowska Karolina. Ocena częstości występowania bólu kręgosłupa oraz stylu i jakości życia wśród osób z bólem kręgosłupa = Evaluation of the prevalence of back pain as well as the style and the quality of life among people with back pain. Journal of Education, Health and Sport. 2016;6(6):329-336. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55609 http://ojs.ukw.edu.pl/index.php/johs/article/view/3586 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Ocena częstości występowania bólu kręgosłupa oraz stylu i jakości życia wśród osób z bólem kręgosłupa Evaluation of the prevalence of back pain as well as the style and the quality of life among people with back pain Piotr Kozłowski1, Katarzyna Kożuch2, Magdalena Kozłowska3, Izabela Ławnicka4, Karolina Kozłowska5 1 Katedra i Zakład Anatomii Prawidłowej Człowieka, UM w Lublinie 2 Uniwersytet Medyczny w Lublinie 3 Katedra i Klinika Neurologii, UM w Lublinie 4 Katedra i Klinika Nefrologii, UM w Lublinie 5 Instytut Filologii Angielskiej, KUL w Lublinie Uniwersytet Medyczny w Lublinie ul. W. Chodźki 1, 20-093 Lublin e-mail: piotr7176@gmail.com Streszczenie Celem pracy była ocena częstości występowania bólu kręgosłupa oraz jakość życia osób z dolegliwościami bólowymi kręgosłupa. W badaniu oceniono również styl życia i poziom natężenia bólu. Badaniem objęto 103 osób. Kobiety stanowiły 56,9% respondentów, natomiast mężczyźni 43,1%. Wiek ankietowanych zawierał się pomiędzy 18 a 75 lat. Badanie przeprowadzono w okresie od stycznia do marca 2016 roku metodą wywiadu standaryzowanego. Narzędziem użytym do zebrania danych, był autorski, anonimowy kwestionariusz. Kwestionariusz zawierał 43 pytania z możliwością jednokrotnego wyboru w tym trzy pytania z możliwością wielokrotnego wyboru. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi- kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Prawie wszyscy ankietowani skarżyli się na dolegliwości bólowe kręgosłupa (93,2%). Ankietowani najczęściej odczuwają dolegliwości bólowe zlokalizowane w odcinku lędźwiowym (75%, p<0,05), następnie kolejno w odcinku szyjnym (44,8%), krzyżowym (38,5%) oraz w odcinku piersiowym (20,8%). Kobiety istotnie statystycznie częściej (p<0,05) wskazywały na ból zlokalizowany w odcinku szyjnym (83,7% ankietowanych w tej grupie). Na pytanie o to czy w czasie doby zmienia się nasilenie bólu 81,3% ankietowanych wskazała, że charakter bólu ulega zmianie w ciągu doby, jest to wartość istotna statystycznie (p<0,05). Z czego 43,8% pytanych wskazała, że ból kręgosłupa ma charakter niejednorodny, zmienia się różnie w ciągu doby. Z powodu bólu kręgosłupa z pomocy Poradni Specjalistycznej korzysta 43,8% ankietowanych. Większość respondentów w tej grupie przyjmowała niesteroidowe środki przeciwbólowe (58,2%) oraz doustne lub dożylne leki steroidowe (37,2%). Słowa kluczowe: ból kręgosłupa, ból pleców, zmiany zwyrodnieniowe kręgosłupa, dyskopatia, styl życia. Abstract The aim of this study was to evaluate the prevalence of back pain in relation to the quality of life of people suffering from this kind of pain. The study also focused on the significance of the correlation between the lifestyle and level of pain intensity. There were 103 respondents involved in the study. The age of the respondents was between 18 and 75 years. The study was conducted in the period from January to March 2016 and it employed the standardized interview method. The tool used for data collection was an anonymous questionnaire produced specifically for this study. The questionnaire consisted of 43 single choice questions and three multiple questions. Statistical analysis was performed using chi-square test. All values for which p <0.05 were considered statistically significant. Almost all respondents complained of back pain (93.2%). The respondents most often felt pain in the lumbar section (75%, p <0.05). The respondents also claimed to suffer from pain in the cervical (44.8%), sacral (38.5%) and the thoracic sections (20.8%). Women significantly more often (p <0.05) indicated pain located in the cervical section (83.7% of respondents in this group). To the question of whether during the day the severity of pain changed, 81.3% of the respondents gave an answer that the nature of pain changed throughout the day (a statistically significant value, p <0.05). Additionally, 43.8% of those respondents indicated that the pain is of a heterogeneous nautre. Due to back pain, 43.8% of the respondents admitted to having to consult a specialist. The majority of this group took non-steroidal analgesics (58.2%) and oral or intravenous steroidal analgesics (37.2%). Keywords: back pain, degenerative changes of the spine, intervertebral discs, lifestyle.